2009
DOI: 10.1063/1.3224124
|View full text |Cite
|
Sign up to set email alerts
|

Metal clusters with hidden ground states: Melting and structural transitions in Al115+, Al116+, and Al117+

Abstract: Heat capacities measured as a function of temperature for Al(115)(+), Al(116)(+), and Al(117)(+) show two well-resolved peaks, at around 450 and 600 K. After being annealed to 523 K (a temperature between the two peaks) or to 773 K (well above both peaks), the high temperature peak remains unchanged but the low temperature peak disappears. After considering the possible explanations, the low temperature peak is attributed to a structural transition and the high temperature peak to the melting of the higher ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…In 40% of the cases, the energy of the clusters increased, but the initial fcc structure, despite some violation of the order of stacking of atomic layers with the formation of icosahedral fragments, persisted up to a temperature T = 370 K, and only further heating led to the forma tion of the icosahedral structure. In this connection, it is necessary to consider the data of the experimental study [29] on the temperature dependence of the heat capacity for the Al 115 , Al 116 , and Al 117 clusters. In [29], it was found that the heat capacity exhibits two well defined peaks at approxi mately 450 and 600 K. However, it was noted that, after heating of the clusters to a temperature above both peaks (773 K) followed by cooling to room tem perature, the repeated measurements of the heat capacity demonstrated the presence of only the high temperature peak of the heat capacity, while the lower temperature peak disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…In 40% of the cases, the energy of the clusters increased, but the initial fcc structure, despite some violation of the order of stacking of atomic layers with the formation of icosahedral fragments, persisted up to a temperature T = 370 K, and only further heating led to the forma tion of the icosahedral structure. In this connection, it is necessary to consider the data of the experimental study [29] on the temperature dependence of the heat capacity for the Al 115 , Al 116 , and Al 117 clusters. In [29], it was found that the heat capacity exhibits two well defined peaks at approxi mately 450 and 600 K. However, it was noted that, after heating of the clusters to a temperature above both peaks (773 K) followed by cooling to room tem perature, the repeated measurements of the heat capacity demonstrated the presence of only the high temperature peak of the heat capacity, while the lower temperature peak disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…39 For annealed clusters, the abrupt changes in the kinetic energy thresholds at around 450 K are expected to disappear and the kinetic energy thresholds below 450 K are expected to be similar to the values above 450 K. However, this has not yet been confirmed experimentally.…”
Section: Discussionmentioning
confidence: 97%
“…There are several possible explanations for the existence of two peaks. 39 They could result from different parts of the clusters melting at different temperatures. For example, surface premelting is a well-known phenomenon that occurs for some metal surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations